Cerebro, modelo A159III - Cranstein scientific gmbh (Alemania Cranstein scientific gmbh)
This human brain model in 8 parts is a great educational tool for teaching and learning about the human nervous system and anatomy of the brain. The detailed brain is delivered on a removable base for easy display in the classroom.
Texto de la descripción de las piezas, en inglés
Material de apoyo a la docencia. Modelo anatómico
Keywords: Anatomía humana; Cerebro -- Maqueta